PENGARUH PENUNDAAN PENGKLEMAN DAN PEMOTONGAN TALI PUSAT TERHADAP KADAR ZAT BESI BAYI BARU LAHIR DI BPM KOTA BENGKULU TAHUN 2015 - Destariyani , Elvi (JURNAL KESEHATAN ALMUSLIM, 2016)
The problem of Iron Deficiency Anemia problem in infants is a serious health problem because it will disturb mental and cognitive development for subsequent developments. One of assumption cause while there is the ICC (Immediately Cord Clamping) in every birth (Indonesian standard used 58 steps of Normal Delivery Care) is 2 minutes after born. Clamping before the baby breathes lead blood suplay to the lungs decreased so resulting hypovolemia. Clamping the umbillical cord immediately will be increasing risk of anemia to the baby. Aims of this research is to determine the effect of delay clamping and cutting umbillical cord to the iron levels of newborns in Midwives Independent Practice in Bengkulu City, 2015.This research started from September until November 2015. Population was all newbornsin Midwives Independent Practice with spontaneous labor without pregnancy complications. Sample for every group were 15 subjects, so amount of 30 subjects. Data taken primery then treated and analyzed with T-Independents test. Result of research showed Haemoglobion level group subjects clamping less then 3 minutes between 9,6 to 15,9 gr% and clamping group less then 3 minutes between 12,6 to 16 gr%. For clamping group more ≤ 3 minutes dan >3 minutes there was significant different between Average hemoglobin subject (12,4gr% ±1,80 and 14,5 gr% ±1,29) with significant value. It need to consider the evaluation of early cord clamping practices that occurred during this especially for the normal childbirth with healthy babies and even months. Extent of the influence of the security cord clamping more then 3 minutes after newborns of normal childbirth.